Concerted Community Engagement: Refugee Education and Parents’ Daily Acts of Resistance - Celia Reddick (Social Sciences)
Around the world, millions of young people and their families navigate education in settings of conflict and displacement. Despite the growing number of refugee families seeking educational opportunities outside their countries of origin, there is scant research on the efforts families undertake to ensure and improve this education. In this study, I seek to understand how families participate in refugee children’s education in displacement. Drawing on interviews with 16 refugee parents and caregivers living in Kakuma Refugee Camp, Kenya, I find that caregivers actively engage in their children’s schooling. Through what I am calling concerted community engagement, families choose, monitor, and supplement schools, working to ensure that refugee children benefit from the education they receive in exile as they build lives in the present and for the future.